Core Skills and Four Primary Applications of the Cross-Body Armlock - Scott, Steve (Revista de Artes Marciales Asiáticas, 2012)
The topic of the article is the four core skills of how to perform the juji gatame (cross-body armlock). The purpose of the article is to present an organized series of skills that are progressively stepped. The reader will better understand the skills of juji gatame and be able to start with a fundamental skill, then progress on to a more complex skill, but all in the context that the four skills presented contitute a core base of technical ability that will help any interested person perform juji gatame more effectively. The skills presented are based on the author’s 42 years of training and coaching and based on the approach taken by numerous European judo and sambo armlock specialists. My conclusion is that if the four core skills presented in this article are sutdies, practiced and developed by the reader, the reader will have not only a better understanding of juji gatame, but also have progesssively better skill in performing the technique, especially in stress or competitive situations.